KELAYAKAN USAHA DENGAN PENDEKATAN ANALISIS SWOT (STUDI KASUS DI RUMAH PRODUKSI SOUVENIR JAVA FIBER JOMBANG) - SITI NUR QOMARIYAH; CHULIYATUL MUFARROHAH (LP2MTBM MAKARIOZ, 2021)
This study aims to identify internal factors and external factors using the SWOT analysis approach to increase sales at theJava Fiber Souvenir Production House Banjardowo Jombang. The method used in this study is the calculation of IFAS andEFAS calculations, SWOT matrix and Grand Strategy Matrix, data obtained from surveys and interviews. Based on theresults of our research at the Banjardowo Jombang Java Fiber Souvenir Production House, the Banjardowo Jombang javaFiber Souvenir Production House is in a quadrant position I where this indicates that the Banjardowo Jombang Java FiberSouvenir Production House is in a very profitable position, From the results of the SWOT analysis, strategies that can beapplied are obtained, namely utilizing technological developments, increasing quality and quantity and expanding marketshare.